Energy System Planning Considering Renewables and Pumped-storage Power Plants. - Jonas C. Costa; Edson C. Bortoni; Paulo A. V. Vieira; Victor A. D. Faria (Department of Electrical Engineering, Institut Teknologi Nasional Malang, Indonesia, 2017)
Renewables will play an important role in the generation for the next decades, but the great problem they face is the intermittency of the natural resource availability, mainly when considering solar and wind generation. In this context, the pumped-storage finds a great opportunity. Its operation consists of two mains mechanisms: to pump water to be stored in an upper reservoir when there is surplus of energy in the system, and to generate as a regular power plant, with the stored water, when there is a lack of energy in the system. This paper presents an introductory with a revision of the world consumption and capacity of 2030 considering the parcel of renewables, and a simulation of several possibilities of the energy mix in various Scenarios. The simulations consider mainly the contribution of pumped-storage hydro. The possible arrangements of construction pumped-storage hydro, costs, and a mathematical model of linear optimization using pumped-storage are analyzed and presented. The developed method is applied to several Scenarios and the conclusions are obtained from that.